A new methodology for crisp equivalent of fuzzy chance constrained programming problem - Nanda, S.; Panda, G.; Dash, J. K. (Fuzzy optimization and decision making, 2008)
This paper deals with a chance constrained programming model, where both fuzziness and randomness are present in the objective function and constraints. The concept of fuzzy random variable, mean and variance of fuzzy random variable, minimum of fuzzy numbers are used in the model. The methodology is verified through a numerical example.